2005
DOI: 10.1016/j.jasms.2005.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the presence and location of t-Boc protecting groups in amines and dipeptides using on-column H/D exchange HPLC/ESI/MS

Abstract: High performance liquid chromatography/mass spectrometry (HPLC/MS) has become a widely used technique for routine analysis of pharmaceutical compounds. The constant search for new drugs requires the development of time-efficient methods that can be employed in high-throughput screening of combinatorial libraries of a variety of compounds, including amines and peptides. Conventional HPLC/MS is a powerful technique that can easily be automated and is suitable for comprehensive screening purposes. However, the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…The early use of deuterium oxide as a mobile phase for ESI LC-MS was demonstrated by Karlsson using a microbore column with L per min flow rates [14]. The use of D 2 O as the mobile phase for regular HPLC at a flow rate 0.2-1.0 mL/min has been demonstrated in several recent publications [4][5][6][7][8][9][10].…”
Section: On-line H/d Exchange Lc-ms Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The early use of deuterium oxide as a mobile phase for ESI LC-MS was demonstrated by Karlsson using a microbore column with L per min flow rates [14]. The use of D 2 O as the mobile phase for regular HPLC at a flow rate 0.2-1.0 mL/min has been demonstrated in several recent publications [4][5][6][7][8][9][10].…”
Section: On-line H/d Exchange Lc-ms Experimental Setupmentioning
confidence: 99%
“…This warrants the development of a convenient method for the fast characterization of its absence or presence in reaction mixtures [9]. LC-MS has become the primary method for such mixture analyses.…”
Section: Determining Presence or Absence Of T-boc Protecting Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…A elucidação da estrutura é concluída com o auxílio de técnicas de RMN bidimensionais (HSQC, HMBC, 1 H-1 H COSY etc.). O HiTSE ainda pode ser utilizado ou adaptado para uso com outras técnicas, tais como HPLC-EM 69 .…”
Section: Conclusões E Perspectivasunclassified
“…Hunt et al reported use of HDX for determining the hydrogens bonded to heteroatoms in alcohols, phenols, carboxylic acids, amines, amides, and mercaptans by CI [23]. Later, the mass spectra of ESI HDX were used to study proteins, peptides, metabolites, and antibiotics [24][25][26][27][28][29]. Recently, atmospheric pressure photoionization (APPI) HDX coupled to MS has been reported [30], and its use for determining the structure of crude oil compounds has been explored [31].…”
Section: Introductionmentioning
confidence: 99%